Liquid metal induced embrittlement of a nitrided clutch shell of a motorbike. (March 2016) - Ding, Ning; Xu, Na; Guo, Weimin; Shi, Junbo; Zang, Qishan; Wu, Chi-Man Lawrence
Abstract: The failure mechanism of a clutch shell made from SPCC nitrided steel was analyzed. The component sustained multiple brittle fractures during assembly. Under SEM examination, the fracture surface was found to have facet and cleavage grain appearance. It was predicted that the cleavage fractures started from sites of intergranular fractures. XRD results showed that the nitriding layer contained Fe3 N (60 wt.%) and Fe4 N (40 wt.%). It is noted that Fe3 N is more brittle than Fe4 N. An impact test was carried out to compare the impact resistance of the failed and normal components. EDS analysis was also carried out, and it was found that the fracture surface contained zinc, which was not an element specified for the SPCC steel or the nitriding salt. As the salt bath nitriding process operated at a temperature higher than the melting point of zinc, failure was most likely due to liquid metal zinc induced embrittlement, as a result of localized salt bath material contamination with zinc. Highlights: Mechanism of multiple brittle fractures of a SPCC shell (nitriding) is analyzed. The cleavage fractures started from sites of intergranular fractures. The fracture surface contains Zn, which is not an element specified for SPCC steel. Nitriding process operated at a temperature higher than the melting point of Zn. The failure is most likely due to liquid metal zinc induced embrittlement.